Cu(ii) coordination polymers with nitrogen catenation ligands for efficient photocatalytic water oxidation. Issue 38 (24th April 2018) - Jiang, Xin; Yang, Bing; Yang, Qing-Qing; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : Cu(ii ) coordination polymers with nitrogen catenation ligands can photocatalyze water oxidation with the highest TOF (1.68 s −1 ) among copper-based photocatalysts. Abstract : A Cu(ii ) coordination polymer, [Cu(tza)2 ] n (Htza, tetrazole-1-acetic acid), was investigated as an efficient water oxidation catalyst in the well-established Ru(bpy)3 2+ /S2 O8 2− (bpy = 2, 2′-bipyridine) photocatalytic system. The turnover frequency (TOF) was measured to be 1.68 s −1, which is the highest among all reported copper-based photocatalytic water oxidation systems.